What Happened in Stockholm? Moses Finley, the Mainz Akademie, and East Bloc Historians - Tompkins, Daniel P. (Hyperboreus, 2015)
The 1960 International Congress of Historical Science at Stockholm was marked by presentations that reﬂected the tensions of the Cold War. For ancient historians, the critical event was the sessions on slavery, when S. Lauffer and F. Vittinghoff delivered ﬁerce attacks on Marxist historiography as they understood it. The structure of the conference precluded responses in kind, so this essay quickly reviews Eastern Bloc historiography from 1930 up to 1960, with particular attention to E. M. Staerman, J. Pecírka, and I. Hahn, concluding that Marxist social and economic history had positive features. In conclusion, the essay takes up the response of M. I. Finley, who was present at the event and developed his own critique of the Mainz Academie and its leader, Joseph Vogt.